OPTIMALISASI INFORMASI PASAR IKAN TONGKOL (AUXIS THAZARD) ANTARA PEKALONGAN DENGAN JAKARTA - Mira Clenia (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2009)
The objective of this research is to analize the eastern little tuna market betweenPekalongan with Jakarta. The result shows that known by natural by loss of Trader inPekalongan because lack of market information, especially the problem of volume akind of fish which step into fish market in Jakarta. Trader in Pekalongan better optimalof market information which the was obtaining of in decision making of purchasing akind of fish. This Information Optimalisation is done by Trader in Pekalongan do notonly getting market information of trader of commissioner of Jakarta and just guard,but can is also obtained to pass trader of other area. Lack of the market informationseen at index of market between market a kind of fish in Pekalongan with Jakartawhich is his value > 1 ( 13,75). Meaning between market a kind of fish in Pekalonganwith Jakarta not inwrought.Key words: eastern little tuna, market information